IMPLEMENTASI KEWARGANEGARAAN EKOLOGIS UNTUK MENINGKATKAN KESADARAN LINGKUNGAN - Aprilianata; Ramadhan, Idang (Universitas Negeri Surabaya, 2025)
This study aims to review empirical research on the implementation of ecological citizenship. Citizen engagement as ecological citizenship is indispensable in supporting the Sustainable Development Goals (SDGs). This is especially important to prepare the younger generation to face the challenges of global climate change. Ecological citizenship is an awareness of caring for nature and the environment based on the rights and obligations of a good citizen. The method used in this research is a systematic literature review using the Prisma protocol. Data were sourced from articles published in the last 10 years and then categorized based on the year of research, type of research, and research instruments used. Data analysis was conducted by extracting meaningful information from the selected literature, identifying findings, and presenting them. The findings of this research show that there are several examples of ecological citizenship implementation strategies implemented in several countries. This study is expected to provide important information to the government and non-government in the implementation strategy of ecological citizenship. Keywords: Citizenship, Ecological Citizenship, Systematic Literature Review